THE PHENOMENOLOGY STUDY ON WORK EXPERIENCE AND CAREER OF BIPOLAR DISORDER SURVIVORS IN SURAKARTA CITY - Kartika Syandra Refriza; Bhimo Rizky Samudro (MESP–FEB UNS, 2021)
This study was conducted to analyze and understand mood changes consisting of a manic phase and a depressive phase, that were experienced by bipolar disorder survivors in Surakarta City. This thing resulted them in having different work and career experiences from normal people in general. This study also aimed to analyze what efforts had been made by bipolar disorder survivors in the city of Surakarta to solve the problems related to their disorders at work and in their careers. The subjects in this study were 11 people, with the details of 1 key informant (psychiatrist), 8 main informants (bipolar disorder survivors), and 2 supporting informants (bipolar disorder caregivers). The data collection techniques in this study used observation, interviews, and documentation techniques. While the data analysis technique used is an interactive analysis model. The validity test of the data used is source triangulation and technique triangulation. The results of this study indicated that mood swings between the manic phase and the depressive phase with their respective cycle lengths, caused bipolar disorder survivors experiencing difficulties in their work and careers. If a bipolar disorder survivor was not treated properly, they would experience impaired work productivity or even become unemployed. On a micro level, the loss of work productivity would affect the income in the life of a bipolar disorder survivor. Meanwhile, on a macro level, if the survivor of bipolar disorder was an unemployed person, it would become a fairly large economic burden for the country. Therefore, efforts were needed for problems related to the effect on their illness on their work and careers, so that could be resolved. It must be done by both from the survivors themselves, as well as from outside the survivors, such as from their closest people or caregivers, from colleagues, or from the social environment of society in general. Keywords: Bipolar Disorder, Work Experience, Manic Phase, Depressive Phase